CORPORATE GOVERNANCE MECHANISM ON THE FINANCIAL STATEMENT FRAUD AMONG LISTED NON-FINANCIAL FIRMS IN NIGERIA (Journal of Global Accounting, 2024)
This study assesses the effect of corporate governance mechanism on financial statement fraud among listed non-financial firms in Nigeria. The study specifically examined the effect of managerial ownership and ownership concentration on financial statement fraud among listed non-financial firms on Nigerian Exchange Group. The study used an ex post facto research design. Ninety-five (95) listed non-financial firms as at 31st December 2022. The study used a purposive sampling technique to select the sample size of seventy-four (74) non-financial listed firms from the population. The study relied on secondary source of data from annual reports and accounts covering a period of 12 years (2011-2022). Ordinary Least Square multiple regression and Binary Logit Regression Technique were used to analyze the data collected for this work through the aid of E-View 9.0 software. The results of the study revealed that managerial ownership and ownership concentration have significant effects on the financial statement fraud among listed non-financial firms in Nigeria. Based on the results and analyses, this study concludes that managerial ownership and ownership concentration have significant effect on the financial statement fraud among listed non-financial firms on the Nigerian Exchange Group (NGX). This study recommended among others based on the findings of this study that management team should be encouraged to invest in the company by buying shares and be part owner of the company and ownership concentration should be encouraged because it has positive significant effect on financial statement fraud among listed non-financial firms in Nigeria.
Keywords: Corporate Governance; Managerial Ownership; Ownership Concentration; Financial Statement Fraud; Listed Non-financial firms